1977
DOI: 10.1111/1523-1747.ep12492633
|View full text |Cite
|
Sign up to set email alerts
|

CHLOASMA, ORAL CONTRACEPTIVES, AND PLASMA IMMUNOREACTIVE Β-Melanocyte-Stimulating HORMONE

Abstract: Plasma immunoreactive beta-melanocyte stimulating hormone (beta-MSH) has been measured in patients taking a progestogen-only oral contraceptive and in patients taking combined estrogen-progestogen therapy, of whom some had chloasma. Plasma levels did not differ significantly from those in a group of age- and sex-matched controls. It is concluded that the pigmentation of chloasma is not due to increased plasma concentrations of immunoreactive beta-MSH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(12 citation statements)
references
References 9 publications
0
11
1
Order By: Relevance
“…It was shown that lesional skin of melasma has higher amounts of melanin in the epidermis and dermis but no increase in melanocyte number, although the melanocytes were larger and more dendritic and produced higher amounts of eumelanin [57]. Elevated levels of estrogen and progesterone are associated with melasma [58] and several studies have shown a stimulating effect of estrogens on tyrosinase activity in cultured melanocytes [38,39].…”
Section: Induction Of Hyperpigmentation -Specific Mechanismsmentioning
confidence: 99%
“…It was shown that lesional skin of melasma has higher amounts of melanin in the epidermis and dermis but no increase in melanocyte number, although the melanocytes were larger and more dendritic and produced higher amounts of eumelanin [57]. Elevated levels of estrogen and progesterone are associated with melasma [58] and several studies have shown a stimulating effect of estrogens on tyrosinase activity in cultured melanocytes [38,39].…”
Section: Induction Of Hyperpigmentation -Specific Mechanismsmentioning
confidence: 99%
“…Some of the patients have been found to have mild ovarian dysfuntion [5]. However, levels of ²-melanocytic-stimulating-harmone have been found to be normal in idiopathic cases and those on oral contraceptive drugs [5,6]. Certain other factors like hepatic dysfunction, nutritional deficiencies and medications have been implicated [3,7].…”
Section: Introductionmentioning
confidence: 99%
“…At first sight it may appear to be a minor condition without vital risk, but clinicians consider it an important cosmetic stigma difficult to treat and that may cause great emotional suffering. Among sexes, women in general are the most affected (90%) whilst men represent only 10% of the cases (1); melasma occurs in 50 -75% of pregnant women (2,3), and particularly in dark skinned women, especially Oriental and Hispanic (4) although it represents a major cosmetic problem for most races. Melasma presents clinically, at all ages, as symmetric hyperpigmented macules, confluent or punctuate, occurring mainly on the cheeks, upper lip, chin and forehead and is the same for both men and women.…”
mentioning
confidence: 99%
“…During pregnancy elevated levels of estrogen, progesterone and MSH especially in the third trimester, have often been found in association with melasma (2,14). Estrogens and progestins may induce hyperpigmentary responses by stimulating of melanogenesis within melanocytes (15).…”
mentioning
confidence: 99%